Carbon Sequestration through Farm forestry: Case from India - Singh, T. P.; Varalakshmi, V.; Ahluwalia, Sudhir K. (Indian Forester, 2000)
Forests constitute both a sink and a source of atmospheric CO2, In developing countries like India, the potential land area available for the implementation of forest management options for carbon conservation and sequestration is constrained by socio-economic circumstances. Farm Forestry involves the growth and management of trees on private lands and this provides an excellent opportunity for carbon sequestration while supplying wood and non-wood products to meet both domestic and market requirements. Under the Farm Forestry programme in the State of Uttar Pradesh in India, nearly 1906.8 million trees have been planted during the period 1979-94 of 1525.44 million are estimated to be surviving. In terms of land coverage, this works out to over one million hectares. This is significant and adds up to nearly 30% of the entire good natural forest cover in U.P. State. It is estimated that nearly 20 million tonnes of Carbon has been sequestered by these Farm Forestry plantations. Government policies and programmes that are supportive of Farm Forestry, could be the major instruments for increasing carbon sequestration from Farm Forestry, thus contributing to the implementation of the Climate Change Policy.